“How Come These Guns are so Tall”:: Anti-corporate Resistance in Marvin Francis’s City Treaty - Cariou, Warren (Studies in Canadian Literature)

(untitled) (The University of New Brunswick, 2006)
With its clever examination of the effects of large corporations, logos, and unfair labour practices upon the lives of urban Native people, Marvin Francis’s City Treaty can be read as a streetwise anti-globalization manifesto for the indigenous world. Francis uses postmodern irony and verbal excess to show how the lives of contemporary Aboriginal people are implicated in complex patterns of symbol, contract, and stereotype that work to keep them in marginal positions. The author’s exploration of what might be called ‘post-corporate’ indigeneity is most readily contextualized in terms of recent currents in visual art, but is also part of a growing trend in Aboriginal literature, as evidenced by recent works by Thomas King and Jeannette Armstrong.